Three Principles to Support Teacher Effectiveness During COVID-19 - Beteille, Tara (World Bank, Washington, DC, 2020)
Effective teachers are irreplaceable in helping students succeed. They facilitate two-way teaching and learning processes, helping students learn content through real time responses to questions, making learning fun, shaping students' attitudes, exemplifying empathy, modeling teamwork and respect, and building student resilience in several ways. Successful teachers work with school management teams and parents to ensure consistent support for students as they transition through school. The sudden closure of schools during COVID-19 has left many teachers across several countries uncertain about their role, unable to use technology effectively to communicate and teach, and unprepared for classroom challenges when schools reopen. The pandemic has brought the need to bridge digital divides into sharp focus, with countries and schools adept at using such technologies facing fewer challenges in meeting learning goals. There can be little doubt that high-quality education is a social experience, requiring routine human interface. Successful teachers are irreplaceable in this task—and will remain so in the foreseeable future—but they need to be supported in multiple ways to be effective in unpredictable circumstances. Given the central role teachers play in student learning, this note outlines three key principles to help governments and their development partners in supporting teacher effectiveness during and in the aftermath of COVID-19. It discusses these principles in relation to the three phases of the World Bank’s COVID-19 education policy response: coping, managing continuity, and improvement and acceleration.1 The three principles are basic and apply regardless of country context.